New science with pulsed muons - development ideas at ISIS - King, P; Cottrell, S; Cox, S; Eaton, G; Hillier, A; Lord, J; Pratt, F; Lancaster, T; Blundell, S (2003)
The ISIS European Muon Facility provides surface muons for condensed matter investigations in a wide range of subject areas. The Facility has been in its present form since 1994, and consists of three experimental areas fed simultaneously using two muon pulses generated every 20ms by the ISIS proton beam. The current spectrometers enable count rates of 20-25 million events per hour; the maximum applied field presently available is 0.45 T. Plans are being developed to provide a new instrument at ISIS to extend the Facility's capabilities. This new spectrometer would have a highly segmented detector array, significantly increasing the available data rate, and would also be equipped with higher longitudinal fields. Such an instrument would offer the possibility of collecting time-differential data more rapidly than is currently possible on either pulsed or continuous sources; this, together with the improved field, would provide a unique facility enabling new science areas to be explored using muSR. The present plan would also lead to an improved time resolution on the existing ISIS instruments through the time slicing of the muon pulses that feed them. We describe the current development ideas and the scientific and technical considerations underlying them, including the effect of the magnetic field on the muon and positron trajectories for particular spectrometer geometries. (C) 2002 Elsevier Science B.V. All rights reserved.